2023
DOI: 10.1155/2023/6042636
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Quinoa and Amaranth Flour on the Qualitative Characteristics of Gluten-Free Cakes

Razieh Hamzehpour,
Asiye Ahmadi Dastgerdi

Abstract: The effect of pseudocereal flour such as quinoa and amaranth in different concentrations (0, 10, 20, and 30%) was investigated in gluten-free cake formulation. Cake containing amaranth and quinoa flour showed higher protein, fat, ash, and fiber content. A30 (30% amaranth) and Q30 (30% quinoa) had the highest values, and the control sample had the lowest values. The moisture content of the gluten-free cakes was not in the range of the Iranian standard. The sample containing 20% quinoa flour showed the highest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Analysis of variance (ANOVA) was performed by SPSS software (ver. 21) at a signifcance level of 0.05 (p < 0.05) [13].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Analysis of variance (ANOVA) was performed by SPSS software (ver. 21) at a signifcance level of 0.05 (p < 0.05) [13].…”
Section: Discussionmentioning
confidence: 84%
“…Sanz-Penella et al [7] showed that replacing wheat four with amaranth increases the amounts of protein, fat, ash, dietary fber, and minerals. According to the fndings of Hamzehpour and Dastgerdi [13], the addition of amaranth four signifcantly increases the fber and protein content of the cake.…”
Section: Chemical Characteristics Of Pastamentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of amaranth and quinoa flour in gluten-free bread formulations has demonstrated a minimal impact on texture and volume, resulting in bread loaves that achieve a 'moderately acceptable' rating in sensory evaluations, thereby assuring their incorporation without compromising overall quality contributing to the production of acceptable gluten-free bread [105,106]. Furthermore, quinoa and amaranth have been used in gluten-free cake formulations at different concentrations (from 0% to 30%) resulting in palatable and healthier products [107].…”
Section: 7mentioning
confidence: 99%